Impact of the Pandemic on Tax Aggressiveness: Analysis of CSR, Audit Quality, and Capital Intensity in IDX Mining Companies - Salsabila Prameswari; Triyani Budyastuti; Yananto Mihadi Putra (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2024)
This study aims to determine the impact of Corporate Social Responsibility (CSR), Audit Quality, and Capital Intensity on tax aggressiveness during the pandemic. Utilizing secondary data from annual financial reports of mining companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021, this quantitative research employs purposive sampling to select a sample of 20 companies. The analytical method used is multiple regression analysis, with data processing performed using SPSS 22 for Windows and Microsoft Excel. The results of this study indicate that Corporate Social Responsibility has a significantly positive effect on tax aggressiveness, suggesting that companies with higher CSR activities tend to exhibit more aggressive tax behaviors. Conversely, Audit Quality shows a significantly negative effect on tax aggressiveness, indicating that higher audit quality is associated with lower levels of tax aggressiveness. Additionally, Capital Intensity is found to have a significantly negative effect on tax aggressiveness, implying that companies with higher capital investments tend to engage in less aggressive tax strategies. These findings highlight the complex interplay between CSR, audit quality, capital intensity, and tax aggressiveness, particularly in the context of the mining sector during the pandemic. The study contributes to the existing literature by providing empirical evidence on how these factors influence tax aggressiveness and offers insights for policymakers and practitioners aiming to enhance corporate governance and tax compliance.